Autoantibody and idiotype profile of lung involvement in autoimmune rheumatic disease. Issue 3 (March 1990) - Turner-Stokes, L; Haslam, P; Jones, M; Dudeney, C; Le Page, S; Isenberg, D
Abstract : Several reports have linked the presence of certain serum autoantibodies with particular clinical manifestations of autoimmune disease. For example, the Jo-1 antibody is now established as a marker for fibrosing alveolitis in polymyositis. To investigate the possible association of further autoantibodies or idiotypes with fibrosing alveolitis in autoimmune rheumatic disease a panel of autoantibodies was measured in serum samples from 28 patients with systemic lupus erythematosus (SLE) (10 with and 18 without lung involvement), 21 patients with scleroderma (12 with fibrosing alveolitis and nine without), and 41 patients with 'lone' fibrosing alveolitis. Antibodies measured were IgM and IgG anti-dsDNA and anti-ssDNA antibody; IgG and IgM anticardiolipin antibody; anti-poly (ADP-ribose) antibody; antibodies to two common idiotypes of anti-DNA antibodies, designated 134 and 16/6; and IgM, IgG, and IgA isotypes of rheumatoid factor. None of these antibodies was specifically associated with lung involvement in SLE or scleroderma, but a trend was found towards an increase in all autoantibodies in association with lung disease in SLE, while the reverse trend was seen in scleroderma.